Structural Elucidation and Toxicity Assessment of Degraded Products of Aflatoxin B1 and B2 by Aqueous Extracts of Trachyspermum ammi - Iram, Wajiha; Anjum, Tehmina; Iqbal, Mazhar; Ghaffar, Abdul; Abbas, Mateen (Frontiers in Microbiology, 2016)
In this study aqueous extract of seeds and leaves of Trachyspermum ammi were evaluated for their ability to detoxify aflatoxin B1 and B2 (AFB1; 100 µg L-1 and AFB2; 50 µg L-1) by In Vitro and In Vivo assays. Results indicated that T. ammi seeds extract was found to be highly significant (P < 0.05) in degrading AFB1 and AFB2 i.e. 92.8% and 91.9% respectively. However T. ammi leaves extract proved to be less efficient in degrading these aflatoxins, under optimized conditions i.e., pH 8, temperature 30˚C and incubation period of 72h. The structural elucidation of degraded toxin products by LCMS/MS analysis showed that eight degraded products of AFB1 and AFB2 were formed. MS/MS spectra showed that most of the products were formed by the removal of double bond in the terminal furan ring and modification of lactone group indicating less toxicity as compared to parent compounds. Brine shrimps bioassay further confirmed the low toxicity of degraded products, showing that T. ammi seeds extract can be used as an effective tool for the detoxification of aflatoxins.